Analisis faktor-faktor yang mempengaruhi pendapatan petani jeruk pamelo di Kabupaten Pati - Ernoiz Antriyandarti; Hanik Muzdalifah; Kusnandar (Fakultas Pertanian Universitas Yudharta Pasuruan, 2023)
The contribution of the pomelo farming revenue to the GRDP of Pati District is very low, about 0.007%. This study aims to determine the factors that affect the income of pomelo farmers in the Pati District. This study was conducted in Bageng Village, Gembong Sub-district, Pati District. By using convenience sampling of 78 respondents. This study applied multiple linear regression analysis. The results shows that the average production and income of each pomelo farm in Pati District is 384 kg/year and IDR6.577.500/year. The average production cost is IDR936.136/year with an average income of IDR5.641.3641/year. The results of regression analysis showed that 99.3% of the income pomelo farming in Pati District could be explained by all the factors. The most influential factor on income is production quantity. The number of trees, production costs, and output price has a positive effect on the income, while the production cost has a negative effect on the farmers. In addition, the factor of age, education, and experience of farmers have not affected the income. Optimization needs to be done by increasing the quantity of production in order to generate optimal income from pomelo farming in Pati District.